2014
DOI: 10.2147/cia.s62597
|View full text |Cite
|
Sign up to set email alerts
|

Risk scores and geriatric profile: can they really help us in anticoagulation decision making among older patients suffering from atrial fibrillation?

Abstract: ObjectivesAnticoagulation for the prevention of cardio-embolism is most frequently indicated but largely underused in frail older patients with atrial fibrillation (AF). This study aimed at identifying characteristics associated with anticoagulation underuse.MethodsA cross-sectional study of consecutive geriatric patients aged ≥75 years, with AF and clear anticoagulation indication (CHADS2 [Congestive heart failure, Hypertension, Age >75, Diabetes mellitus, and prior Stroke or transient ischemic attack] ≥2) up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…The CGA did not individualize any factor associated with PAI prescription. To our knowledge, such findings have never been published for PAI, but similar results were found for anticoagulants in a geriatric setting [40]. We found no link between motor disability or falls and the prescription of PAI.…”
Section: Factors Associated With Pai Prescriptionssupporting
confidence: 85%
“…The CGA did not individualize any factor associated with PAI prescription. To our knowledge, such findings have never been published for PAI, but similar results were found for anticoagulants in a geriatric setting [40]. We found no link between motor disability or falls and the prescription of PAI.…”
Section: Factors Associated With Pai Prescriptionssupporting
confidence: 85%
“…Studies looking into OAC prescription rates in frail people have been variable. While practices in countries such as Australia and Mexico have shown that frailty status predicted OAC use in older adults (109, 116) there is also evidence to suggest a lack of association between the two (117, 118). This is likely a reflection of the variations in practice and guideline recommendations between the regions as well as the perception of frailty by those assessing it.…”
Section: Frailtymentioning
confidence: 99%
“…It has been reported that decreased kidney function and lower hemoglobin levels are associated with an increased risk for new-onset AF, especially when both are present [ 35 ]. On the other hand, thrombocytopenia is associated with an increased risk of hemorrhage [ 36 , 37 ]. In HAS-BLED, bleeding refers to previous bleeding history and/or predisposition to bleed (i.e.…”
Section: Evidence and Recommendationsmentioning
confidence: 99%